Risk Factors Associated with End-Stage Renal Disease (ESRD) in Patients With Atherosclerotic Renal Artery Stenosis: A Nationwide Population-Based Analysis - Yu, Tung-Min (Medicine (Baltimore), 2015)
The aim of this study was to investigate the risk factors associated with end-stage renal disease (ESRD) in patients with atherosclerotic renal artery stenosis (ARAS). Information about the study participants was extracted from the National Health Insurance Research Database of Taiwan for the years 1999 through 2011. We conducted this retrospective cohort study of patients with ARAS to identify the potential risk factors associated with long-term renal outcomes. A total of 2184 patients with ARAS were enrolled, of whom 840 had ESRD and were classified as the study group, and 1344 patients who were without ESRD were included in the comparison cohort. After adjusting for related variables, univariable, and multivariable logistic regression analysis showed that ESRD was associated with higher Charlson-comorbidity index (CCI) score (adjusted odds ratio [OR] = 6.78, 95% CI = 4.59–10.0 for CCI = 2; adjusted OR = 20.0, 95% CI = 13.7–29.2 for CCI ≥3), diabetes (adjusted OR = 1.55, 95% CI = 1.24–1.93), hypertension (adjusted OR = 3.66, 95% CI = 2.36–5.66), and age 20 to 49-years old (adjusted OR = 2.14, 95% CI = 1.51–3.03). Moreover, our data showed that renal artery revascularization (RAR) was significantly associated with a lower risk of ESRD in ARAS patients (crude OR = 0.64, 95% CI = 0.50–0.84). Our study is the first to disclose that CCI score was significantly associated with the risk of ESRD in ARAS patients, and comorbid diseases including diabetes mellitus and hypertension significantly affect renal outcomes in patients with ARAS. Of note, our data showed that renal artery revascularization was associated with a lower risk of ESRD in ARAS patients in long-term follow-up.